Comparison of Seismicity Between the Subduction Zone and Local Fault Zone in the Bali Island Region During the 1963–2023 Period Using the Likelihood Method - Nainggolan, Putri Srimalemta; Winardi Tjahyo Baskoro; I Gusti Ketut Satria Bunaga; I Ketut Sukarasa; Nyoman Wendri; I Ketut Putra (Universitas Hamzanwadi, 2025)
Research has been conducted on the comparison of seismicity between the subduction zone and the local fault zone in the Bali Island region during the 1963–2023 period. This research aims to compare the b-value, a-value, seismicity index, and earthquake recurrence period between the subduction zone and the local fault zone. The research was conducted within the observation boundaries of 114,4°–115,7° East Longitude and 11,4°–8,8° South Latitude. The research was carried out at the Center for Meteorology, Climatology, and Geophysics Region III Denpasar using the likelihood method for earthquakes with magnitude ≥ 3,3. The data used were obtained from the official websites of the USGS (United States Geological Survey) and BMKG, with depths ≤ 600 km for the subduction zone and depths ≤ 35 km for the local fault zone. The results show that the subduction zone has a b-value of 0,534 and an a-value of 4,599, while the local fault zone has a b-value of 0,829 and an a-value of 5,087. The seismicity index in the subduction zone ranges from 0,289–13,046 with an earthquake recurrence period of 0,077–3,459 years. Meanwhile, in the local fault zone, the seismicity index ranges from 0,126–8,366 with an earthquake recurrence period of 0,212–7,949 years. Earthquake distribution is dominated in the subduction zone at 82,63% compared to the local fault zone at 17,37%.